Third-Party BK Virus-Specific Cytotoxic T Lymphocyte Therapy for Hemorrhagic Cystitis Following Allotransplantation. Issue 24 (20th August 2021) - Olson, Amanda; Lin, Ruitao; Marin, David; Rafei, Hind; Bdaiwi, Mustafa H.; Thall, Peter F.; Basar, Rafet; Abudayyeh, Ala; Banerjee, Pinaki; Aung, Fleur M.; Kaur, Indresh; Abueg, Glorette; et al.
Abstract : PURPOSE: BK virus-associated hemorrhagic cystitis (BKV-HC) is a common complication of allogenic hematopoietic stem cell transplantation (AHSCT), particularly in recipients of alternative donor transplants, which are being performed in increasing numbers. BKV-HC typically results in painful hematuria, urinary obstruction, and renal dysfunction, without a definitive therapeutic option. METHODS: We performed a clinical trial (ClinicalTrials.gov identifier: NCT02479698 ) to assess the feasibility, safety, and efficacy of administering most closely HLA-matched third-party BKV-specific cytotoxic T lymphocytes (CTLs), generated from 26 healthy donors and banked for off-the-shelf use. The cells were infused into 59 patients who developed BKV-HC following AHSCT. Comprehensive clinical assessments and correlative studies were performed. RESULTS: Response to BKV-CTL infusion was rapid; the day 14 overall response rate was 67.7% (40 of 59 evaluable patients), which increased to 81.6% among evaluable patients at day 45 (40 of 49 evaluable patients). No patient lost a previously achieved response. There were no cases of de novo grade 3 or 4 graft-versus-host disease, graft failure, or infusion-related toxicities. BKV-CTLs were identified in patient blood samples up to 3 months postinfusion and their in vivo expansion predicted for clinical response. A matched-pair analysis revealed that, compared with standard of care, after accounting for prognostic covariate effects, treatment with BKV-CTLs resulted in higher probabilities of response at all follow-up timepoints as well as significantly lower transfusion requirement. CONCLUSION: Off-the-shelf BKV-CTLs are a safe and effective therapy for the management of patients with BKV-HC after AHSCT.